Particulate polyphosphate and alkaline phosphatase activity across a latitudinal transect in the tropical Indian Ocean. (30th January 2018) - Martin, Patrick; Lauro, Federico M.; Sarkar, Amit; Goodkin, Nathalie; Prakash, Satya; Vinayachandran, P. N.
Abstract: Polyphosphate (polyP) is an essential chemical constituent of microbial cells, and is hypothesized to play important roles in the marine biogeochemistry of phosphorus. However, polyP has only rarely been measured in the oceans. Here, we present data on the distribution of polyP across a latitudinal transect in the tropical Indian Ocean. PolyP concentrations (quantified as molar equivalents of a synthetic polyP standard) and ratios of polyP to total particulate phosphorus (TPP) along the transect ranged between 3–7 nmol eq. L −1 (polyP concentration) and 0.2–0.4 nmol eq. nmol −1 (polyP : TPP ratio), which is very similar to values reported from the North Pacific Subtropical Gyre. Yet unlike in the North Pacific, soluble reactive phosphorus was depleted to low concentrations (≤ 0.03 μmol L −1 ), and alkaline phosphatase activity was relatively high (1–4 nmol P L −1 h −1 ) along our cruise track. We attribute these results to the unique seasonal changes in iron and macronutrient supply in the Indian Ocean, which are caused by the monsoonal reversal in ocean currents. PolyP concentrations and polyP : TPP ratios decreased sharply with depth down to 150 m, suggesting that polyP was preferentially recycled relative to TPP, unlike in the North Pacific Subtropical Gyre. We hypothesize that alkaline phosphatase exerts a significant control over marine polyP biogeochemistry.